Semantic categorization in bilinguals: A typicality effect - Lagishetti, Sampath Kumar; SP, Goswami (Journal of All India Institute of Speech and Hearing)
Semantic categorization is mainly to understanding of concepts using meaning and based on sets of characteristics properties. Better exemplars of category are identi ed quicker compared to poorer exemplars, is termed as ypicality e ect". Clothing and non-clothing stimuli (strong and weak exemplars) were used for semantic categorization on 10 monolingual and 10 bilingual normal participants. NeuroScan Inc. data acquisition system gentask program was used to measure reaction time. All participants were instructed to press the appropriate option in response pad for all stimuli. Comparison of reaction time between monolingual and bilingual groups and comparison between rst language and second language in bilinguals was measured. Results showed that a typicality e ect was observed in both monolinguals and bilinguals and no di erences were observed between clothing and non-clothing stimuli except in one category. Also results showed signi cant di erence between languages in bilingual groups.